Relationship of the measurement and surrogates of low energy availability with blood biomarkers in a sample of national team youth athletes - Ayala-Guzmán, C. I.; Ortiz-Hernández, L.; Silva-Quiróz, V.; de Lucio-Ávila, V. H.; Nájera-Medina, O.; Bojalil, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Measuring of low energy availability (EA) could be time-consuming and complex. Hence, low EA surrogates (LEAS) are an alternative to assess health and performance risks. Youth athletes are an understudied population in this topic. We aimed to measure EA, to estimate the prevalence of LEAS, and examine their relationship with blood biomarkers in a sample of National Team youth athletes. Forty-eight adolescents (58.3% males) of three sports (boxing, n=17; weightlifting, n=18; and diving, n=13) participated in the study and were asked to maintain their eating habits and training loads. We collected fasting blood samples (sex hormones, creatinine, cytokines, and uric acid) and estimated fat-free mass using a prediction equation (Ortiz-Hernández et.al., 2017). We calculated energy intake with the ASA-24 software (National Cancer Institute, 2023) using data from foods and drinks ingested during the previous month. We estimated linear regression models for each participant to predict VO2 and VCO2 from heart rate based on information obtained by resting and cardiopulmonary exercise tests using indirect calorimetry. Linear regression models were used to estimate exercise energy expenditure using the heart rate recorded during training. Participants completed four inventories to assess LEAS (Melin et.al., (2014); Unikel et.al., (2004); Davis et.al., (2007); McNulty et.al., (2001)). We performed descriptive analyzes and Pearson correlation coefficients. Mean EA was 32.1 ±19.5 kcal/kg/day. There were no differences in EA between sports (p>0.05). The most common symptoms of LEAS before a major competition were gastrointestinal (80.8%) or menstrual (38.3%) dysfunction, dizziness (31.9%), cold sensitivity (29.8%), injuries (27.6%), illness (25.5%). One out of five of athletes had risk eating behaviors. LEAF-Q score was positively related to testosterone (0.46, p<0.05) but negatively related to progesterone (-0.264, p=0.072), stress score was negatively related to progesterone (-0.34, p<0.05). EA measurement and the remaining LEAS scores were not related to blood biomarkers (p>0.05). Most youth athletes experienced at least one symptom of LEAS before a major competition. These subjective experiences were related to sex-hormones. Unexpectedly, direct measurement of EA was not related to blood biomarkers.